The progress of miR-205 regulating apoptosis in cancer - Chai, Dandan; Du, Hua; Shi, Yingxu (Frontiers in Oncology, 2025)
MicroRNAs (miRNAs) constitute a class of small non-coding RNAs that play a pivotal role in post-transcriptional gene regulation. The dysregulation of miRNAs has been widely implicated in the pathogenesis of diverse human cancers. Among these, miR-205 has attracted considerable attention owing to its aberrant expression patterns in multiple cancer types, where it regulates tumor initiation and progression via diverse molecular mechanisms. Apoptosis, a fundamental biological process essential for cellular homeostasis, represents a tightly regulated form of programmed cell death that significantly influences cancer development under both physiological and pathological conditions. In malignant cells, miR-205 exhibits a dual regulatory role by modulating apoptosis-related signaling pathways and their downstream target genes, thereby displaying both oncogenic and tumor-suppressive functions. This comprehensive review systematically explores recent advances in understanding the functional role of miR-205 in apoptosis regulation across a spectrum of human malignancies and highlights its potential therapeutic implications for future cancer therapies.